The generation and evaluation of TKO/hCD55/hTM/hEPCR gene-modified pigs for clinical organ xenotransplantation - Guoli Huai; Yong Wang; Jiaxiang Du; Zhenhui Cheng; Yuxuan Xie; Jia Zhou; Hongmei Tang; Yanyan Jiang; Xiangyang Xing; Shaoping Deng; Dengke Pan; Dengke Pan; et al. (Frontiers in Immunology)
IntroductionGenetically edited pigs, modified using CRISPR-Cas9 technology, hold promise as potential sources for xenotransplantation. However, the optimal combination of genetic modifications and their expression levels for initial clinical trials remains unclear. This study investigates the generation of TKO/hCD55/hTM/hEPCR (6GE) pigs and evaluates their compatibility with human immune and coagulation systems.MethodsThe 6GE pigs were generated through iterative genome editing and F1 generation breeding. Genotyping, flow cytometry, and immunohistochemistry confirmed the knockout of GGTA1, CMAH, and B4GALNT2. Expression levels of human genes (hCD55, hTM, hEPCR) were quantified. In vitro assays using aortic endothelial cells (pAECs) from 6GE pigs assessed human serum IgM and IgG binding, complement cytotoxicity, and thrombin-antithrombin (TAT) complex levels. Blood from gene-edited pigs was used for pathophysiological analysis.ResultsComplete knockout of GGTA1, CMAH, and B4GALNT2 was confirmed in 6GE pigs. The expression of hCD55 and hTM was approximately seven and thirteen times higher than in humans, respectively, while hEPCR levels were comparable to those in humans. In vitro, 6GE pAECs showed significantly reduced binding of human IgM and IgG compared to wild-type pAECs (IgG p<0.01, IgM p<0.0001). Similar to TKO/hCD55 pAECs, 6GE pAECs exhibited a substantial reduction in complement-mediated cytotoxicity (p<0.001) compared to TKO pAECs. Co-expression of hTM and hEPCR in 6GE pigs led to a significant decrease in thrombin-antithrombin (TAT) complex levels in co-culture with human whole blood, compared to WT (p<0.0001), TKO (p<0.01), and TKO/hCD55/hTM pigs (p<0.05). Pathophysiological analysis demonstrated excellent compatibility of 6GE pig kidneys and livers with human immune and coagulation systems. However, 6GE pigs showed increased susceptibility to infection compared to other gene-edited pigs, while TKO/hCD55 pigs were considered safe when they were all bred in a general environment.DiscussionHighly expressing hCD55, along with the co-expression of hEPCR and hTM genes, is expected to effectively reduce human complement cytotoxicity and enhance anticoagulant efficacy in genetically modified pigs. The 6GE pigs exhibited robust compatibility with human physiological and immune systems, fulfilling the criteria for clinical trials. Furthermore, it is imperative to rear donor pigs in pathogen-free (DPF) facilities to mitigate infection risks and prevent the transmission of porcine pathogens to humans.